Fatigue properties of notched specimens made of FeP04 steel - Rozumek, D.; Marciniak, Z. (Фізико-хімічна механіка матеріалів, 2011)
Fatigue properties of the specimens with different notches made of FeP04 steel are presented. The specimens ware characterized by double symmetric lateral notches with a notch root radius ranging from ρ = 0.2 to 10 mm. The MTS 809 servo-hydraulic device was used for tests. All fatigue tests were performed under force control, by imposing a constant value of the nominal load ratio (R = 0) and a load amplitude Pa = 6 kN for the notch root ρ = 0.2 mm and 7 kN for the notch root ρ = 1.25; 2.5 and 10 mm. The test frequency varied from 13 and 15 Hz. During the tests under constant load fatigue weakening of the material and an increase in strain were observed. Подані втомні властивості зразків з подвійними симетричними боковими вирізами (радіуси концентратора від ρ = 0,2 до 10 mm) з сталі FeP04. Для випробувань використовували сервогідравлічний пристрій МТС 809. Втомні випроби виконані за постійного номінального коефіцієнта навантаження (R = 0), амплітуди навантаження 6 kN для радіуса концентратора ρ = 0,2 mm і 7 kN для радіусів ρ = 1,25; 2,5 і 10 mm. Частота навантаження 13...15 Hz. Під час випробувань з постійним втомним навантаженням спостерігали знеміцнювання матеріалу зі збільшенням деформованості. Представлены усталостные свойства образцов с двойными симметричными боковыми вырезами (радиусы концентратора от ρ = 0,2 до 10 mm) из стали FeP04. Для испытаний использовали сервогидравлическое устройство МТС 809. Усталостные испытания выполнены при постоянном значении номинального коэффициента нагружения (R = 0), амплитуде нагружения 6 kN для радиуса концентратора ρ = 0,2 mm и 7 kN для радиусов ρ = 1,25; 2,5 и 10 mm. Частота нагружения изменялась в пределах от 13 до 15 Hz. Во время испытаний с постоянным усталостным нагружением наблюдалось разупрочнение материала и увеличения деформируемости.